2021
DOI: 10.1371/journal.pone.0247414
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wearing facemasks on oxygenation and ventilation at rest and during physical activity

Abstract: Background Facemasks are recommended to reduce the spread of SARS-CoV-2, but concern about inadequate gas exchange is an often cited reason for non-compliance. Research question Among adult volunteers, do either cloth masks or surgical masks impair oxygenation or ventilation either at rest or during physical activity? Study design and methods With IRB approval and informed consent, we measured heart rate (HR), transcutaneous carbon dioxide (CO2) tension and oxygen levels (SpO2) at the conclusion of six 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 10 publications
5
47
1
11
Order By: Relevance
“…For example, in a sample of 50 adults (one-third of which has an underlying co-morbidity), no episodes of hypoxemia or hypercarbia occurred. No differences in CO 2 or oxygen saturation (SpO 2 ) could be detected between baseline values and those measured while exercising (walking briskly for ten minutes) when wearing a mask [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a sample of 50 adults (one-third of which has an underlying co-morbidity), no episodes of hypoxemia or hypercarbia occurred. No differences in CO 2 or oxygen saturation (SpO 2 ) could be detected between baseline values and those measured while exercising (walking briskly for ten minutes) when wearing a mask [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that both groups (EXP and CON) showed different results for RPE, which was not in line with the scholarly literature. For example, Morris et al [ 28 ] showed that physiological strain or thermal discomfort did not differ between prolonged facemask-use and the control condition. Only perceived dyspnea was found to significantly differ between the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, claims pertaining to decreased oxygen saturation are unfounded. Recent studies assessing medical masks and cloth face coverings in the general adult population have not demonstrated major physiologic changes related to gas exchange [454,455,[556][557][558][559][560][561].…”
Section: Policymaking About Masks and Issues With Compliance And Mandates In The Communitymentioning
confidence: 99%
“…Auf S. 362 wird die Frage CO 2 -Retention unter der Maske aufgegriffen. Es ist richtig, dass es dazu keine Studien bei Kindern gibt, wohl aber bei Erwachsenen, die keine Hinweise auf CO 2 -Retention zeigen [ 2 ]. In der Diskussion wird auf eine mögliche pathophysiologische Hypothese, warum bei Kindern diese Effekte anders, sogar schwerwiegender sein sollten, nicht eingegangen.…”
Section: Erwiderungunclassified